2015
DOI: 10.1093/mutage/geu055
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of male versus female responses in the Pig-a mutation assay

Abstract: Validation of the Pig-a gene mutation assay has been based mainly on studies in male rodents. To determine if the mutagen-induced responses of the X-linked Pig-a gene differ in females compared to males, 7- or 14-week old male and female Sprague Dawley rats were exposed to N-ethyl-N-nitrosourea (ENU). In the study with the 7-week old rats, exposure was to 0, 1, 5 or 25mg ENU/kg/day for three consecutive days (study Days 1-3). Pig-a mutant phenotype reticulocyte (RET(CD59-)) and mutant phenotype erythrocyte (RB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…It is therefore important to verify that the lyonization process in females does not introduce any unexpected problems with the conduct of the Pig-a assay. Our present data and that of previous reports (9-10) demonstrate that female rats are similarly responsive to genotoxic agents and show the same kinetic behavior as male rats. Thus, we believe that integration of the Pig-a assay with routine toxicology testing has the major advantages of eliminating the need for any additional animals for genotoxicity evaluation while at the same time providing sensitive genotoxicity information in both sexes, and in the context of relevant information on toxicity, pharmacokinetics, and metabolism that is routinely assessed as part of toxicity studies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It is therefore important to verify that the lyonization process in females does not introduce any unexpected problems with the conduct of the Pig-a assay. Our present data and that of previous reports (9-10) demonstrate that female rats are similarly responsive to genotoxic agents and show the same kinetic behavior as male rats. Thus, we believe that integration of the Pig-a assay with routine toxicology testing has the major advantages of eliminating the need for any additional animals for genotoxicity evaluation while at the same time providing sensitive genotoxicity information in both sexes, and in the context of relevant information on toxicity, pharmacokinetics, and metabolism that is routinely assessed as part of toxicity studies.…”
Section: Discussionsupporting
confidence: 88%
“…Labash et al . reported that while spontaneous frequencies were similar between the sexes, three consecutive days of exposure at 25 mg ENU/kg/day caused modest quantitative differences in young male versus female Sprague Dawley rats, possibly related to differences in hematopoietic activity (10). …”
Section: Introductionmentioning
confidence: 99%
“…No clear sex bias has been found for Pig‐a mutation in rodent studies (Labash et al ; Labash et al ), while studies in different ethnic human populations have produced inconsistent results (Dobrovolsky et al ; Dertinger et al ; Cao et al ). The Pig‐a gene is on the X chromosome, suggesting that X‐chromosome inactivation in females may affect spontaneous MFs.…”
Section: Discussionmentioning
confidence: 99%
“…Le séquençage du gène PIG-A réalisé sur des cellules issues de patients HPN et de sujets sains a ainsi identifié plus de 100 mutations inactivantes (parmi lesquelles des mutations non-sens, faux-sens, des décalages du cadre de lecture, des substitutions, et de larges délétions) aboutissant toutes au même phénotype de déficience en GPI, suggérant que le gène PIG-A puisse être sensible à un grand nombre de modes d'actions génotoxiques [15,34]. Deux lacunes identifiées par l'IWGT en 2015 ont été comblées par la publication de deux études récentes : les performances du test ne dépendent en fait pas du nombre de copies du chromosome X portées par l'individu, les fréquences spontanées et induites de cellules mutées pour le gène PIG-A n'étant pas différentes entre mâles et femelles [23,35,36] ; l'érythropoïèse compensatoire observée après exposition à un agent hémolysant non génotoxique (comme le 2-butoxyéthanol) n'entraîne pas d'augmentation de la fréquence des cellules GPI-déficientes [37]. Ces qualités ont initié l'évaluation du test PIG-A in vitro : le séquen-çage du gène PIG-A réalisé sur des lymphoblastes humains cultivés in vitro et soumis à divers génotoxiques connus, a révélé des résultats comparables à ceux obtenus in vivo chez la souris après exposition aux mêmes agents [38].…”
Section: Cytométrie De Fluxunclassified